2014
DOI: 10.1308/003588414x13946184902000
|View full text |Cite
|
Sign up to set email alerts
|

Unintended consequences of policy change to watchful waiting for asymptomatic inguinal hernias

Abstract: Introduction In 2009 the Department of Health instructed McKinsey & Company to provide advice on how commissioners might achieve world class National Health Service productivity. Asymptomatic inguinal hernia repair was identified as a potentially cosmetic procedure, with limited clinical benefit. The Birmingham and Solihull primary care trust cluster introduced a policy of watchful waiting for asymptomatic inguinal hernia, which was implemented across the health economy in December 2010. This retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…A 2014 study reported on clinical consequences after the inception of a watchful waiting strategy. 141 Regionally, a WW policy was instituted in the United Kingdom for those with asymptomatic IHs. Outcomes of approximately 1000 patients before, and 1000 patients after, the policy’s inception were compared retrospectively.…”
Section: Indications: Treatment Options For Symptomatic and Asymptomamentioning
confidence: 99%
“…A 2014 study reported on clinical consequences after the inception of a watchful waiting strategy. 141 Regionally, a WW policy was instituted in the United Kingdom for those with asymptomatic IHs. Outcomes of approximately 1000 patients before, and 1000 patients after, the policy’s inception were compared retrospectively.…”
Section: Indications: Treatment Options For Symptomatic and Asymptomamentioning
confidence: 99%
“…Eight Clinical Commissioning Groups in England and Wales (15%) subsequently required a history of incarceration and/or that the hernia to increase in size each month before surgery should be considered 65 , which Sanders and Kurzer 62 considered "a draconian and impractical requirement". A study published in 2014 66 examined the effect of a local policy change for asymptomatic inguinal hernias. Patients underwent watchful waiting instead of elective repair.…”
Section: Eq-5dmentioning
confidence: 99%
“…• Observation may be a safe alternative for male patients with comorbidities that increase surgical risk and those with poorly symptomatic or asymptomatic hernia, but it is noteworthy that the latter subgroup has a 70% chance of developing symptoms throughout observation and ultimately requiring surgical treatment. Many patients can be securely observed, with a very low probability of developing complications, such as incarceration and requiring urgency operation, with increased morbidity 3,4 .…”
Section: Conservative Versus Operative Managementmentioning
confidence: 99%